Radiation-induced nondisjunction. - Uchida, I A (1979)
The methodology and results of epidemiological studies of the effects of preconception diagnostic x-rays of the abdomen on chromosome segregation in humans are described. Many studies have been conducted in a number of different countries. The vast majority show the same positive, though not significant, trend to increased nondisjunction among the offspring of irradiated women. The results of the various studies, however, cannot be pooled because of differing methodologies used. A worldwide co-operative project with standardized methodology is recommended. Such a study should identify the parental origin of the nondisjunctional event before etiological factors are investigated. Abnormal chromosome segregation during mitotic division has been inducted experimentally by the in vitro exposure of human lymphocytes to a low dose of 50 R gamma irradiation. First meiotic nondisjunction has been successfully induced by whole body exposure of female mice to a low dose of radiation. Further experiments are being conducted to try to induce abnormal segregation during second meiotic division. Because of difficulties encountered in trying to estimate total gonad doses resulting from differing techniques employed by radiologists and other health personnel, no attempt has been made to estimate the doubling dose nor minimum safe dose regarding the effects of radiation on chromosome segregation in humans. The question of time-related repair of the mechanism involved in chromosome segregation is raised.